Perspektif Sosial Budaya dalam Perkembangan Sejarah Kebangsaan Nasional - Haryono Rinardi (Endogami: Jurnal Ilmiah Kajian Antropologi, 2020)
This article which titled Socio-Cultural Perspective in the Development of National History tries to discuss the development of Indonesian Nationality from a socio-cultural perspective. The Indonesian nation was not born through a natural process. However, there was a political process that was mutually agreed upon by all of Indonesian. The awareness and willingness are available between them to unite and to establish the Nation and the State of Indonesia. It can happen because in Indonesian society there is a changing tolerance, flexibility and open tolerance towards other cultures